Energy saving through load balancing of 3-wire loads - Abdulkareem Mokif Obais; Ali Abdulkareem Mukheef (International Journal of Electrical and Computer Engineering (IJECE), 2023)
In this paper, static var compensators (SVCs) and many load compensation techniques are reviewed. A continuously and linearly controlled compensating susceptance is devised from a switched capacitor bank and a switched reactor bank. The switched capacitor bank is built of four binary weighted thyristor switched capacitors, while the switched reactor bank is built of three binary weighted thyristor switched reactors. Although few switched capacitors and reactor are used, their binary weighted values beside their control scheme make them respond as a continuously and linearly controlled reactive device in capacitive and inductive modes of operation. A load balancing system is constructed of three identical devised compensating susceptances connected in delta-form. It is designed for balancing an 11 kV 50 Hz distribution station. The proposed system is designed and tested on PSpice which is a computer program equivalent in performance to real hardware design. The simulation results of the proposed system have showed significant treatment of severe imbalance conditions.